Learning Design Cooperative Learning Inside-Outside Circle in Indonesian Language Lessons at Madrasah Ibtidaiyah: A Literature Review - Iin Herlina; Agus Suryana; Muhamad Azhar Alwahid (Tarbiatuna: Journal of Islamic Education Studies, 2022)
The writing of this article aims to find out the design of the inside-outside circle cooperative learning learning design, namely, 2. The advantage of the Inside Outside Circle technique is that there is a clear structure and allows students to share with different partners briefly and regularly. In addition, students work with fellow students in a cooperative atmosphere and have many opportunities to process information and improve communication skills. The steps for the design of the inside-outside circle cooperative learning technique in Indonesian lessons are that half of the students form a small circle facing out, the other half form a large circle facing in, students facing each other share information simultaneously, students who are in the outer circle rotate then share information with their (new) friends in front of them, and so on.This research method uses the library method by analyzing various books and journals related to the application of the Inside-Outside Circle cooperative learning technique. The conclusions concluded that: 1. learning techniques with the system of inner and outer circles (Inside-Outside Circle) where students share information with each other at the same time with different pairs briefly and regularly.2. The advantage of using the IOC method is that students will easily get different and varied information at the same time. Meanwhile, the steps for implementing the inside-outside circle cooperative learning design in Indonesian lessons are: as follows: 1) The first step, half the class stands in a small circle and faces out. 2) The second step, the other half of the class forms a circle outside the first circle and faces inward. 3) The third step, then two students in pairs from small and large circles share information. This information exchange can be done by all partners at the same time. 4) The fourth step, students in the small circle stay in place, while students in the large circle move one or two steps clockwise, so that each student gets a new partner. 5) The last step, it is the turn of students who are in the big circle to share information. And so on. Keywords: cooperative learning, Inside Outside Circle, Indonesian Lesson, speaking skills